Illocutionary Acts in the Film Cruella by Craig Gillespie: A Pragmatics Study - Tazkia Isnaeni Nur; Ervina CM Simatupang (Budapest International Research and Critics University, 2022)
Speech acts are utterance that functions to say or inform something and do something. This utterance also emerges in film transcription. This research is focused on analyzing the illocutionary speech acts in Cruella the movie produced in 2021. Several theories are applied in this research, especially Searle (1997) which focusing on the illocutionary acts and Leech (1998) about relationship between the meaning spoken by the individual and situations of pronunciation or referred to as (speech situations). The method used in this research is qualitative method by implementing several procedures to obtain data. There are five types of illocutionary speechlessness in the Cruella film. First, there are 5 data assertive speech acts (16.67%); Second, directives speech acts as much as 7 data (23.33%); Third, commissive speech acts are 6 data (20%); Fourth, there are 8 data expressive speech acts (26.67%); Fifth, the illocutionary speech acts of declarations are 4 data (13.33%). The dominant type of tutor act in the film Cruella (2021) is the illocutionary commissive speech act, which is 8 data (26.67%). Based on analysis, there are 30 whole scenes, the first function, namely competitive, was found quite a lot with 9 utterances (30%). In the second function, namely the convivial function, the authors found 6 (20%). In the third function, namely collaborative, researchers found 8 (26.67%). In the last function, namely conflictive function, the researcher found 7 (23.33%). The function of most illocutionary speech acts in the film Cruella (2021) is the competitive function, namely with 9 utterances (30%).